2017
DOI: 10.3892/mco.2017.1376
|View full text |Cite
|
Sign up to set email alerts
|

There is no relationship between SOD2 Val-16Ala polymorphism and breast cancer risk or survival

Abstract: Abstract. Breast cancer is the most common diagnosed cancer among females worldwide. Superoxide dismutase 2 (SOD2), an antioxidant enzyme, may break the balance between the oxidant and antioxidant system to induce various diseases. The present study aimed to clarify the association between the SOD2 Val-16Ala polymorphism and breast cancer risk or survival. Thus, a meta-analysis of the relevant articles retrieved from PubMed and EMBASE databases was conducted to illuminate the association with odd ratios (ORs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…48 The Val16Ala SNP, which alters enzyme structure and localization into the mitochondria, has been suggested to affect breast cancer susceptibility, although this is not supported by the current epidemiological literature. 49 Since superoxide and hydrogen peroxide are also key reactants of ironcatalyzed formation of hydroxyl radicals, 2 an interaction between iron and MnSOD is biologically plausible and supported by a study on dietary iron intake and prostate cancer risk. 50 However, our study provided no evidence of such interactions, possibly because the variant (alanine) with higher MnSOD enzyme activity, and presumably greater antioxidant capacity, has also been suggested to increase intracellular iron accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The Val16Ala SNP, which alters enzyme structure and localization into the mitochondria, has been suggested to affect breast cancer susceptibility, although this is not supported by the current epidemiological literature. 49 Since superoxide and hydrogen peroxide are also key reactants of ironcatalyzed formation of hydroxyl radicals, 2 an interaction between iron and MnSOD is biologically plausible and supported by a study on dietary iron intake and prostate cancer risk. 50 However, our study provided no evidence of such interactions, possibly because the variant (alanine) with higher MnSOD enzyme activity, and presumably greater antioxidant capacity, has also been suggested to increase intracellular iron accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike GSTs, MnSOD is a mitochondrial enzyme that plays a role in antioxidant defense by catalyzing the conversion of superoxide anions to hydrogen peroxide . The Val16Ala SNP, which alters enzyme structure and localization into the mitochondria, has been suggested to affect breast cancer susceptibility, although this is not supported by the current epidemiological literature . Since superoxide and hydrogen peroxide are also key reactants of iron‐catalyzed formation of hydroxyl radicals, an interaction between iron and MnSOD is biologically plausible and supported by a study on dietary iron intake and prostate cancer risk .…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest a complex interaction between endogenous SOD2, that has become a prooxidant, and exogenous antioxidants, such as lycopene and MSKE, that was utilized in this study. Finally, meta-analysis from PubMed and EMBASE databases and relevant cancer studies determined that there was no relationship or association of risk between SOD2 and breast cancer [ 48 ]. We observed that the outlined studies were all conducted clinically in patients; and the in vivo and in vitro differences may play a critical role.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on SOD2 have focused on a functional variant (rs4880, previously known as rs1799725) where a substitution of valine by alanine (Val16Ala) influences protein expression and function, possibly due to decreased mRNA stability [43]. Breast cancer survival studies have been inconsistent, but a recent meta-analysis combined results across eight studies and found no relationship between this functional SOD2 variant and breast cancer survival [44]. In the current analysis, we found that higher SOD2 expression was associated with better OS, and no other studies have specifically evaluated TNBC outcomes.…”
Section: Discussionmentioning
confidence: 99%